2015
DOI: 10.1016/j.acalib.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

No Budget, No Experience, No Problem: Creating a Library Orientation Game for Freshman Engineering Majors

Abstract: "Mystery at the Library" is a simple, inexpensive game developed as a library orientation activity for freshman engineering students. Players searched the library building and online to find clues and solve the mystery of a stolen book. Feedback from players and library desk staff was used to improve the game over time. A straightforward narrative with puzzles focused on learning objectives kept players engaged and avoided unnecessary confusion. A post-game survey indicated that the game was both helpful and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…Results show that GBL enhanced the students' achievement and motivation, but that there was no influence on efficiency depending on learning styles. Giles (2015) developed the game named "Mystery at the Library" in accordance with the learning styles with the intent to inform engineering students about the potentials of the university library. A sample of 44 students was interviewed, and it was concluded that the students positively reacted to the game and were positively motivated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that GBL enhanced the students' achievement and motivation, but that there was no influence on efficiency depending on learning styles. Giles (2015) developed the game named "Mystery at the Library" in accordance with the learning styles with the intent to inform engineering students about the potentials of the university library. A sample of 44 students was interviewed, and it was concluded that the students positively reacted to the game and were positively motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Rezultati su pokazali da igre izrađene za obrazovne svrhe povećavaju stupanj motivacije i postignuća učenika, ali nije utvrđen utjecaj na učinkovitost igranja povezan sa stilom učenja. Giles (2015) je izradio igru "Misterij u knjižnici" u skladu sa stilovima učenja i s namjerom upoznavanja studenata strojarstva s potencijalom sveučilišne knjižnice. Intervjuirana su 44 studenta te je zaključeno da su studenti pozitivno reagirali na igru i da su bili pozitivno motivirani.…”
Section: Raspravaunclassified
“…The literature has shown that introducing activities that enhance collaboration, such as games, has increased student learning (Leach and Sugarman, 2006). Current literature suggests that games in library instruction are an effective method for addressing various learning styles and focusing on games that combine real-world exploration of introducing library services with a fictional narrative (Giles, 2014). The challenge for any instruction librarian is to create favorable learning conditions so that students may acquire information literacy knowledge (Walker, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies regarding active learning exercises such as scavenger hunts, treasure hunts, Amazing Library Races, mysteries in the library, and self-guided library tours on mobile devices have also shown success in library orientations. They provide low-pressure games that introduce library locations and research concepts, without the high stakes of a graded class research assignment (Giles, 2015;Foley & Bertel, 2015;Broussard, 2010;Burke & Lai, 2012;Kasbohm, Schoen, & Dubaj, 2006;McCain, 2007;Marcus & Beck, 2003;Cahoy & Bichel, 2008;Boss, Angell, & Tewell, 2015). Additionally, Pike and Alpi (2015) found that students "prefer to have the opportunity to experience library tools and resources on their own devices, which they were more likely to use in the future" (para.…”
Section: Library Orientations For First-year Studentsmentioning
confidence: 99%
“…Unfortunately, scavenger hunts used as library orientations have a poor reputation among academic librarians and can easily devolve into busy-work where dozens of students mob the reference desk with the same set of often badly-designed or out-ofdate questions, frustrating both students and librarians alike (McCain, 2007;Rugan & Nero, 2013;Ly & Carr, 2010;Giles, 2015). However, Rugan and Nero (2013) "hinted at the potential of such hunts if thoughtfully constructed" (p. 7), and McCain (2007) found that well-designed library scavenger hunts support their effectiveness as a teaching tool.…”
Section: Library Orientations For First-year Studentsmentioning
confidence: 99%